IMPROVING STUDENTS’ READING COMPREHENSION OF RECOUNT TEXT THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION - Hazibah, Hazibah; Apriliaswati, Rahayu; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to improve the students’ reading comprehension on recount text through Cooperative Integrated Reading and Composition (CIRC) method, especially identifying details of story elements, understanding of simple past tense, and vocabulary.  CIRC is one of the methods of cooperartive learning strategies to teach reading and writing consisting of three main activities: basal related activities, direct instruction in reading comprehension, and integrated languages arts and writing. This action research was conducted in three cycles. The data were derived from reading comprehension test, observation checklist, and field note. The subjects were 25 students in SMP N 3 Sambas in Academic Year 2015/2016. The data revealed that the students were enthusiastic and active in the class. The result of this research showed that CIRC could improve the students’ reading comprehension after three cycles. Using question and answer cards in story grammar and story related writing, the students could improve their ability in finding the detail information in term orientation, event, and re-orientation of recount text. The students could improve understanding of simple past tense by correcting mistakes. Finally, the students could improve vocabulary mastery using vocabulary card. The students’ mean score improve from 68.48 to 75.28, and up to 80.64. Key words: CIRC, Reading Comprehension, Recount Text